Phosphorous-doped graphitic material as a solid acid catalyst for microwave-assisted synthesis of beta-ketoenamines and baeyer-villiger oxidation - Maity, Sayantan; Ram, Farsa; Dhar, Basab Bijayi (ACS Omega, 2020)
Synthesis of phosphorous-doped graphitic materials (P-Gc) using phytic acid as a precursor was done in a microwave oven in a cost- and time-effective green way. The material was used as a solid acid catalyst for microwave (MW)-assisted synthesis of beta-ketoenamines and Baeyer-Villiger (By) oxidation. In the case of BV oxidation, hydrogen peroxide (H2O2) was used as a green oxidant. For beta-ketoenamines, in most cases, 100% conversion with an similar to 95% yield was achieved in ethyl acetate medium. In solvent-free conditions, the yield of beta-ketoenamines was similar to 75%. A kinetic study suggested that the resonance stabilization of the positive reaction center happens in the transition state for beta-ketoenamine synthesis. In BV oxidation, cyclic ketones were converted to their corresponding cyclic esters in good to high yields (similar to 80% yield) in a shorter reaction time (6-20 min). As per our knowledge, this is the first report of BV oxidation catalyzed by a heteroatom-doped graphitic material. For BV oxidation, the phosphoric acid functional groups present in P-Gc might increase the electrophilicity of the carbonyl group of the ketones to compensate for the weakness of H2O2 as a nucleophile and a spiro-bisperoxide intermediate has been identified in high-resolution mass spectrometry.